Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe TPS Menggunakan Soal Hots Terhadap Hasil Belajar Matematika Siswa Materi Kekongruenan dan Kesebangunan - Zaki, Ahmad; Nurhaliza, Ratih; Sahid, Sahid (Issues in Mathematics Education (IMED), 2025)
This research aims to determine whether there is an effect of implementing the think pair share type cooperative learning model using HOTS questions on students' mathematics learning congruence and similarity in Class IX of SMP Negeri 1 Ampana Tete. This research is experimental research. The population is all class IX students of SMP Negeri 1 Ampana Tete for the 2022/2023 academic year. The sample for this was 28 students in class IX A and 28 students in class IX B. The experimental class applied the think pair share type cooperative learning model and the control class applied the conventional learning model. The research instruments used were implementation sheets and learning outcomes tests. The data technique uses learning tests, namely pretest and posttest. The research results show that the class using the Think Pair Share (TPS) cooperative learning model using HOTS questions obtained an average score of 50.07, while the control class taught using the conventional model had an average score of 40.85. The results of the hypothesis test show that H0 is rejected and H1 is accepted, thus it can be concluded that the Think Pair Share (TPS) cooperative learning model has a significant and significant influence on students' mathematics